Beheading the Hydra: counterinsurgent violence and insurgent attacks in Iraq - Eastin, Joshua (Terrorism and political violence, 2018)
We evaluate the effectiveness of anti-insurgent violence as a means to suppress insurgency with micro-level data from the Iraq War. Our findings suggest that while violence against insurgents increases the incidence of future insurgent attacks, the intensity of this violence can significantly influence the outcome. Rather than shifting monotonically, the effect is actually curvilinear, first rising, and then contracting. We argue that at low to moderate levels, violence against insurgents creates opportunities for these groups to signal strength and resolve, which enables them to build momentum, heighten civilian cooperation, and diminish political support for counterinsurgency efforts in these forces’ home countries. The result is an escalation in insurgent attacks. However, at higher levels, this effect should plateau and taper off as insurgent attrition rises, and as civilian fears over personal safety displace grievances that might otherwise provoke counter-mobilization. Our empirical tests on data from the Iraq War, 2004-2009, demonstrate robust support for this argument.